Crystal structures and dielectric properties of two salts of nickel-bis-1, 2-dithiolene with noncentrosymmetric organic cations. (15th November 2018) - He, Jin-Yu; Chen, Xuan-Rong; Qian, Yin; Liu, Jian-Lan; Ren, Xiao-Ming
Graphical abstract: Two nickel-bis-1, 2-dithiolene salts, [1, 4-dimethyl-DABCO][Ni(mnt)2 ] (1) and (TMSF)2 [Ni(mnt)2 ] (2) (mnt 2− = maleonitriledithiolate, 1, 4-dimethyl-DABCO 2+ = 1, 4-dimethyl-1, 4-diazoniabicyclo[2.2.2]octane and TMSF + = trimethylsulfonium) were synthesized and characterized by single crystal structures. The two salts show similar packing structure and display analogous dielectric behavior and two steps of dielectric relaxations in the higher temperature regime. Abstract: Two nickel-bis-1, 2-dithiolene salts, [1, 4-dimethyl-DABCO][Ni(mnt)2 ] (1) and (TMSF)2 [Ni(mnt)2 ] (2) (mnt 2− = maleonitriledithiolate, 1, 4-dimethyl-DABCO 2+ = 1, 4-dimethyl-1, 4-diazoniabicyclo[2.2.2]octane and TMSF + = trimethylsulfonium), were synthesized and characterized by elemental analysis, IR spectra, thermal analysis and single crystal structures. Both1 and2 crystallize in monoclinic space group C2/c, with a formula and cell parameters of C16 H18 N6 NiS4, a = 16.9688(8) Å, b = 9.3003(5) Å, 13.4090(6) Å and β = 103.244(2)° for1 at 293 K versus C14 H18 N4 NiS6, a = 17.108(3) Å, b = 10.2932(16) Å, 14.071(2) Å and β = 118.845(4)° for2 at 293 K. Moreover, two salts show similar packing structure, with the arrangements of alternating layer of anions and cations, and the layers are parallel to the crystallographic ab -plane. Both1 and2 display analogous dielectric behavior, which dielectric permittivity is almost a constant with ε ′ ≈ 12 at the temperature below 270 K for1 versus 215 K for2, and two steps of dielectric relaxations appear in the higher temperature regime, which originate from the molecular dipole orientation and the ion migration.